Ghostly past, capitalist presence a social history of fear in colonial Bengal - Bhattacharya, Tithi ca. 20./21. Jh. (Durham London Duke University Press, 2024)
"In Ghostly Past, Capitalist Presence, Tithi Bhattacharya maps the role that Bengali ghosts and ghost stories played in constituting the modern Indian nation, and the religious ideas seeded therein, as it emerged in dialogue with European science. Bhattacharya introduces readers to the multifarious habits and personalities of Bengal's traditional ghosts and investigates and mourns their eventual extermination. For Bhattacharya, British colonization marked a transition from the older, multifaith folk world of traditional ghosts to newer and more frightening specters. These 'modern' Bengali ghosts, borne out of a new Rationality, were homogenous specters amenable to 'scientific' speculation and invoked at séance sessions in elite drawing rooms. Reading literature alongside the colonial archive, she uncovers a new reordering of science and faith from the middle of the nineteenth century. Bhattacharya argues that these shifts cemented the authority of a rising upper caste colonial elite who expelled the older ghosts in order to recast Hinduism as the conscience of the Indian nation. In so doing, Bhattacharya reveals how capitalism necessarily reshaped Bengal as part of the global colonial project"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Religion and science -- India -- Bengal -- History -- 19th century; Ghosts -- India -- Bengal -- History; Ghost stories, Bengali -- History and criticism; HISTORY / Asia / South / India; RELIGION / Hinduism / General; Asiatische Geschichte; Colonialism & imperialism; HIS062000; HISTORY / Social History; Hinduism; Hinduismus; Kolonialismus und Imperialismus; POL045000; POL054000; Politics & government; Politik und Staat; Asian History; Social & Cultural History; Sozial- und Kulturgeschichte; Bengal (India) -- History -- 19th century; Bengal (India) -- Civilization -- 19th century; Bengal (India) -- Colonial influence; India -- History -- British occupation, 1765-1947; India; Westbengalen